The Impact of Sleep Apnea on Postoperative Utilization of Resources and Adverse Outcomes - Memtsoudis, Stavros G (2014)
BACKGROUND: Despite the concern that sleep apnea (SA) is associated with increased risk for postoperative complications, a paucity of information is available regarding the effect of this disease on postoperative complications and resource utilization in the orthopedic population. With an increasing number of surgical patients suffering from SA, this information is of high importance to physicians, patients, policymakers and administrators alike. METHODS: We analyzed hospital discharge data of patients who underwent total hip or knee arthroplasty (THA, TKA) in approximately 400 United States hospitals between 2006 and 2010. Patient, procedure, and healthcare-system related demographics and outcomes such as mortality, complications, and resource utilization were compared amongst groups. Multivariable logistic regression models were fit to assess the association between SA and various outcomes. RESULTS: We identified 530,089 entries for patients undergoing THA and TKA. Of those, 8.4% had a diagnosis code for SA. In the multivariate analysis, the diagnosis of SA emerged as independent risk factor for major postoperative complications (OR 1.47 (95% CI 1.39;1.55)). Pulmonary complications were 1.86 (95% CI 1.65; 2.09) times more likely and cardiac complications 1.59 (95% CI 1.48; 1.71) times more likely to occur in patients with SA. In addition, SA patients were more likely to require ventilatory support, utilize more intensive care, step-down and telemetry services, consume more economic resources, and require increased lengths of hospitalization. CONCLUSIONS: The presence of SA represents a major clinical and economic challenge in the postoperative period. More research is needed to identify SA patients at risk for complications and develop evidence-based practices in order to aid in the allocation of clinical and economic resources.